A benchmarked automated progress measurement system for haptic motor rehabilitation. (29th June 2009) - Kayyali, Ruba; Shirmohammadi, Shervin
As Haptic devices become more affordable and economical, research in Haptic-based virtual rehabilitation systems is gaining more interest. In addition to the benefits provided by virtual rehabilitation, Haptics offer force and tactile feedback which can be crucial for much upper and lower extremity rehabilitation. In this paper, we present such a system that provides a rich media environment for motor rehabilitation of stroke patients. The system can be used by Occupational Therapists (OTs) to measure and monitor the progress of rehab patients. This is an expanded version of a paper presented at the 3rd IEEE International Workshop on Medical Measurements and Applications, 9?10 May 2008, Ottawa, ON, Canada.